Perjanjian Penyelesaian Utang Bantuan Likuiditas Bank Indonesia (BLBI) Dengan Penyerahan Aset: (Studi Putusan Mahkamah Agung Nomor 1555 K/PID.SUS/2019) - Febrian Rizki Pratama; Sahruddin Sahruddin (Fakultas Hukum Universitas Mataram, 2022)
This research aims to find out the debt settlement agreement of Bank Indonesia Liquidity Assistance (BLBI) with delivery asset which released Syafruddin Arsyad Tumenggung from all lawsuit. The method of this research is normative legal research using statute, conceptual, and case approaches. The result of this research experienced that debt settlement agreement of Bank Indonesia Liquidity Assistance (BLBI) with delivery asset is an agreement which is created by human. The consideration of Supreme Court Judges to Syafruddin Arsyad Tumenggung which was released from all lawsuits due to the agreement, therefore the appropriate settlement is in the civil court.